The Relevance of High-Risk Prisons to Indonesia’s Preventing Violent Extremism Policy - Maulana, Iwa (Perspectives on terrorism, 2022)
Since 2017, the Indonesian Government has established the operation of high-risk prisons for terrorists to prevent radicalization and end the formation and consolidation of terrorist groups in prisons. The operations of high-risk prison are based on the concept of super maximum-security prison, which focuses on security, movement restrictions, and high-level supervision of inmates. This approach makes the aspect of rehabilitation in high-risk prisons less dominant than the security aspect. Therefore, there is a concern that the willingness of terrorist convicts to change is not driven by the success of the intervention programs, but is the result of a brutalist building design and a very tight security system. The long-term consequence of this is that many terrorists tend to be willing to cooperate with the authorities just to get out of high-risk prisons as quickly as possible. However, in many cases their attitudes and behavior basically might not have changed.